Bacterial exudates as growth‐promoting agents for the cultivation of commercially relevant marine microalgal strains. Issue 6 (18th July 2022) - Sauvage, Justine; Wikfors, Gary H.; Dixon, Mark S.; Kapareiko, Diane; Sabbe, Koen; Li, Xiaoxu; Joyce, Alyssa
Abstract: In laboratory and industrial cultivation of marine microalgae, it is customary to enrich cultures with macronutrients (N, P), chelated trace metals, and vitamins at ~10 4 × concentrations found in nature to obtain high culture densities. Other naturally occurring growth‐promoting compounds found in local seawater are not enriched and remain at environmental concentrations. Microalgae may thus be deprived of the mutualistic contributions of co‐occurring microorganisms with which they have evolved complex chemical relationships. In the present study, we assess the direct (mixed bacteria–microalgae cultivation) and indirect (exposure to exudates only, without physical contact) effects of 10 bacterial strains on the growth of five marine microalgal strains used as feeds in marine aquaculture hatcheries. Bacterial strains were selected based upon previously reported growth‐promoting characteristics in plants or microalgae, or known release of probiotics. Our experiments demonstrate superior stimulation of microalgal growth by bacterial exudates, and without the presence of the bacteria that produced these exudates. However, response to bacterial exudate enrichment was dependent upon the microalgae strain and bacterial pairing. Exudates from Bacillus, Mesorhizobium, and Phaeobacter strains were most effective, with 22%–69% increases in microalgal specific growth rate. Such findings indicate that bacterial exudates accelerate rate‐limiting processes governing nutrient acquisition, assimilation, or anabolism, and possibly algal release of exopolymeric substances. Maximal cell density, however, remained constrained by macronutrient limitation. Scaled‐up trials in an oyster hatchery confirmed the practical benefit of bacterial exudate culture medium enrichment and demonstrated the suitability of exudate‐enriched microalgae to feed hatchery‐reared bay scallops. This work presents a promising strategy to improve microalgal culture media formulations using bacterial exudate components as growth promoters, and is the first such study to identify specific pairings with relevance for aquaculture production.